2021
DOI: 10.1108/jiabr-09-2019-0177
|View full text |Cite
|
Sign up to set email alerts
|

Sukuk and monetary policy transmission in Indonesia: the role of asset price and exchange rate channels

Abstract: Purpose The purpose of this study is to empirically analyze the role of sukuk in the monetary policy transmission mechanism through the asset price and exchange rate channels in the Indonesian economy. Design/methodology/approach Using the monthly data from January 2003 to November 2017, this study uses a multivariate vector error correction model causality framework. To examine the role of sukuk in the monetary policy transmission mechanism through the asset price channel, this study uses the variables of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…This shows the contribution variable this to growth economy enough exhilarating. Finding this supported by Suriani et al, (2021) found that sukuk has a connection in upgrade growth economy through policy variable monetary as level interest and price share through asset price and value exchange. Finding interaction dynamic between sukuk and variables economy other give implication important policy for development domestically, especially in the sukuk market in the global Islamic capital market.…”
Section: Long-term Estimate and Short-term Estimation Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This shows the contribution variable this to growth economy enough exhilarating. Finding this supported by Suriani et al, (2021) found that sukuk has a connection in upgrade growth economy through policy variable monetary as level interest and price share through asset price and value exchange. Finding interaction dynamic between sukuk and variables economy other give implication important policy for development domestically, especially in the sukuk market in the global Islamic capital market.…”
Section: Long-term Estimate and Short-term Estimation Resultsmentioning
confidence: 82%
“…Several studies have looked into the numerous connections between capital market developments and Indonesia's economic growth. According to Suriani et al, (2021), sukuk has a two-way causal link with economic growth through asset prices and exchange rate channels, however there is no causal association between Sukuk and inflation through asset prices and exchange rate channels. Through asset prices and exchange rate channels, sukuk are also explained to have a causal relationship with monetary policy variables, interest rates, and stock prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research related to the effectiveness of the transmission of Islamic monetary policy has been widely carried out. The findings yielded in significant positive and negative results (Hassan et al, 2021;Selim, 2020;Suriani et al, 2021).…”
Section: ~339~mentioning
confidence: 97%
“…Empirical studies that analyze the factors that influence fluctuations in stock markets in several countries have been carried out by previous economists, such as monetary policy factors (Mishkin, 1978;Majid and Yusof, 2009;Gregoriou et al, 2009;Laopodis, 2010;Hojat and Sharifzadeh, 2017;Suriani et al, 2021;Tomar and Kesharwani, 2022). In addition to monetary policy, the source of economic fluctuations that is considered important is uncertainty (Bloom, 2009;Christiano et al, 2014;Gilchrist et al, 2014;Dery and Serletis, 2021).…”
Section: Introductionmentioning
confidence: 99%